2009
DOI: 10.1186/bf03352914
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical investigation of seamounts near the Ogasawara Fracture Zone, western Pacific

Abstract: This paper provides an analysis of multi-channel seismic data obtained during 2000-2001 on seamounts near the Ogasawara Fracture Zone (OFZ) northwest of the Marshall Islands in the western Pacific. The OFZ is unique in that it is a wide rift zone that includes many seamounts. Seven units are delineated on the basis of acoustic characteristics and depth: three units (I, II, and III) on the summit of seamounts and four units (IV, V, VI, and VII) in basins. Acoustic characteristics of layers on the summit of guyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The height of the load is calculated by adding the thickness covered by the sediment to the exposed height of seamount. The total sediment thickness is determined to be 600 m in the OFZ and 500 m in the PB based on the drilled cores and the previous seismic profiles (Wedgeworth & Kellogg 1987; Abrams et al 1992; Larson et al 1992; Lee et al 2008). This thickness estimate of the sediment layer does not account for the isostatic effects of sediment loading.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The height of the load is calculated by adding the thickness covered by the sediment to the exposed height of seamount. The total sediment thickness is determined to be 600 m in the OFZ and 500 m in the PB based on the drilled cores and the previous seismic profiles (Wedgeworth & Kellogg 1987; Abrams et al 1992; Larson et al 1992; Lee et al 2008). This thickness estimate of the sediment layer does not account for the isostatic effects of sediment loading.…”
Section: Methodsmentioning
confidence: 99%
“…Smoot (1983, 1989) suggested that the Dutton Ridge in the OFZ formed as a volcanic plateau at the extinct triple junction of the Phoenix, Farallon and Pacific plates and this once‐continuous plateau was then fractured and faulted to produce the present group of guyots and ridges. Lee et al (2005, 2008) investigated the acoustic characteristics and mass‐wasting with chirp subbottom and seismic data over the seamounts near the OFZ.…”
Section: Geological Settingsmentioning
confidence: 99%